2018
DOI: 10.1186/s13049-018-0528-8
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of medical dispatch - a systematic review

Abstract: BackgroundIt is a challenge to dispatch Emergency medical Services (EMS) appropriately with limited resources and maintaining patient safety; this requires accurate dispatching systems. The objective of the current systematic review was to examine the evidence, according to GRADE, for medical dispatching systems to accurately dispatch EMS according to level of acuity and in recognition of specific conditions.A systematic search was performed trough PubMed, Web of Science, Embase (free text in all fields), Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
2
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(113 citation statements)
references
References 36 publications
(89 reference statements)
4
101
2
6
Order By: Relevance
“…All data were recorded in a standardized case form (standard clinical history used by the EMS). During the first EMS contact with the patient, the ERN recorded: Administrative data; times of arrival, assistance, and evacuation; reason for calling according to the Advanced Medical Priority Dispatch System [24,25]; the set of vital signs (respiratory rate, oxygen saturation, use of supplemental oxygen, heart rate, systolic blood pressure, temperature, and level of consciousness); and the pLA value.…”
Section: Data Abstractionmentioning
confidence: 99%
“…All data were recorded in a standardized case form (standard clinical history used by the EMS). During the first EMS contact with the patient, the ERN recorded: Administrative data; times of arrival, assistance, and evacuation; reason for calling according to the Advanced Medical Priority Dispatch System [24,25]; the set of vital signs (respiratory rate, oxygen saturation, use of supplemental oxygen, heart rate, systolic blood pressure, temperature, and level of consciousness); and the pLA value.…”
Section: Data Abstractionmentioning
confidence: 99%
“…5 GoodSAM, 1 CurtainRd, London, UK. 6 South East Coast Ambulance Service NHS Foundation Trust, Crawley, UK.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…This may result in a delayed or inaccurate dispatch. Previous studies have shown that mechanism of injury together with interrogation by the dispatcher had a sensitivity of 80.2% and under-triage of 19.7% for the identification of major trauma [6,7], and a Dutch study showed an overall over-triage of 44% [8].…”
Section: Introductionmentioning
confidence: 96%
“…Without accurate measurement and classification of the prevalence (pre-test probabilities) of severe patient conditions, neither the positive or negative predictive values nor the rates of underor over-triage are interpretable. Finally, measurement is also imprecise because there is no consensus on common standards for reporting, particularly on the reference standard against which to compare the dispatch decision [16].…”
Section: Introductionmentioning
confidence: 99%